ANTIBACTERIAL TEST OF Basil (Ocimum sanctum) LEAF EXTRACT AND FRACTION ON Escherichia coli BACTERIA GROWTH - Becerang, Sri Ayumi (LPPM Universitas Bina Mandiri Gorontalo, 2023)
This study aims to determine the effect of basil leaf extract and fraction in inhibiting the growth of Escherichia coli bacteria and to determine the best concentration in inhibiting the growth of Escherichia coli bacteria. The method in this study used a completely randomized design (CRD) with five treatments and five repetitions based on each extract and fraction treatment group, namely: 25% concentration, 50% concentration and 75% concentration. The results showed that from each concentration used from the extract and fraction group, it was found that the largest concentration in inhibiting Eschericia coli bacteria was at a concentration of 75% in the extract group. Statistical analysis of data using the Kruskal Wallis method showed a significant difference in values ​​between extracts and fractions, so it was continued by using the Post Huc Duncan test. Keywords : Basil, Extract, Fraction, Escherichia coli